Insights into the Bending Effect in Premixed Turbulent Combustion Using the Flame Surface Density Transport. Issue 5 (3rd June 2019) - Ahmed, Umair; Chakraborty, Nilanjan; Klein, Markus
ABSTRACT: The bending effect of turbulent flame speed variation (i.e., the deviation from the linear increase of flame speed with increasing root-mean-square turbulent velocity fluctuation) has been investigated based on a Direct Numerical Simulation database of statistically planar turbulent premixed flames propagating into forced unburned gas turbulence. The validity of Damköhler's first hypothesis has been utilized to analyze the bending effect in terms of generalized Flame Surface Density (FSD) evolution. The volume-integrated value of the tangential strain rate term of the FSD transport equation remains positive, whereas the volume-integrated value of the curvature term assumes negative values. Under statistically stationary state, the positive value of the volume-integrated tangential strain rate term remains in equilibrium with the negative value of the volume-integrated curvature term. It has been found that the contribution of the normal strain rate to the flame surface area remains negative for small turbulence intensities, which eventually become positive for large turbulence intensities. This is a consequence of the change of collinear alignment of the reaction progress variable gradient from the most extensive principal strain rate direction to the direction of the eigenvector associated with the most compressive principal strain rate with increasing turbulence intensity. An increase in turbulence intensity increases the width of the probability density functions of flame curvature, and thereby increases the surface-averaged curvature squared values. This eventually makes the FSD curvature term due to the tangential diffusion component of displacement speed as the major contributor to the negative contribution of the volume-integrated curvature term in the FSD transport equation for large turbulence intensities. However, the negative contribution of the volume-integrated FSD curvature term does not increase indefinitely with increasing turbulence intensity and the inner cut-off scale, which also limits the maximum possible value of the volume-integrated FSD strain rate term under statistically stationary state, governs the maximum possible destruction of flame surface area. It has been argued that the upper limits of the flame surface area generation and destruction are responsible for the bending effects in the variations of turbulent flame speed and flame surface area.